Dermatomycosis among Elementary School Children in Jatinangor West Java - Sukmara, Isni Maulina; Miliawati, Risa; Sukandar, Hadyana (Althea Medical Journal, 2015)
Background: Dermatomycosis often occurs in tropical countries. Many studies from tropical countries haveÂ reported high prevalence of dermatomycosis among elementary school children. Despite being a tropicalÂ country, prevalence of dermatomycosis among elementary school children in Indonesia is still unknown.The objective of this study was to determine the prevalence and characteristics of dermatomycosis amongÂ elementary school children in Jatinangor, Sumedang, West Java in SeptemberâNovember 2012.Methods: This study used a cross-sectional descriptive survey method. The 328 children from fiveÂ elementary schools in Jatinangor were included in the study using multistage sampling technique. MedicalÂ history and physical examination was performed to all subjects. Subjects who had skin lesion suspected fordermatomycosis were examined with direct microscopic examination using 10% solutions of potassiumÂ hydroxide (KOH). Data were presented as frequent analysis distribution using Statistical Package for SocialÂ Sciences (SPSS) version 17.0.Results: Of 328 children (174 males, 154 females; aged 5â14 years), 35 (10.6%) had lesions suggestive ofÂ dermatomycosis but only 5 children (1.5%) were positive for dermatomycosis. Males are more prevalentÂ females, patients were in â¥10 years age group. Four cases were Pityriasis versicolor, while one wasÂ diagnosed with tinea facialis.Conclusions: Dermatomycosis among elementary school children in Jatinangor had a low prevalence, withÂ only 4 cases of Pityriasis versicolor and one tinea facialis case. [AMJ.2015;2(1):268â75]